A Mini-Review on the Insight into the Effect of Natural and Synthetic α,β-Unsaturated Carbonyl-Containing Compounds on PI3K/AKT/mTOR Signaling Pathways to Treat Breast Cancer - Kelvin Wong, Khai Voon; Ahmad Mahfuz, Gazali; Normaiza, Zamri; Kamal, Rullah; Mohd Fadhlizil Fasihi, Mohd Aluwi (World Scientific Publishing Co Pte Ltd, 2022)
Breast cancer, which has been one of the most frequently diagnosed cancers worldwide for decades, continues to defy treatment. While researching a remedy to this problem, it was discovered that mTOR has a strong association with breast cancer. Uncontrolled activation of mTOR is shown in a variety of different cancer, making it a critical target for cancer treatment. Inhibition of the mTOR protein kinase can cause autophagic cell death. It is known that covalent inhibitors have become a prominent issue in drug discovery, with covalent inhibitors focusing on α,β-unsaturated carbonyl molecules. Structural modifications to α,β-unsaturated carbonyl may be one of the finest avenues for developing the best breast cancer medication. This review article discusses recent research on natural and synthetic α,β-unsaturated carbonyls and their anti-cancer properties targeting on mTOR, with SAR to showcase the efficacy of synthetic natural products compared to parental compounds using both biological assays and in silico studies.